Synergistic inhibition effect on methane/air explosions by N2-twin-fluid water mist containing sodium chloride additive. (1st October 2019) - Pei, Bei; Li, Jie; Wang, Yan; Wen, Xiaoping; Yu, Minggao; Jing, Guoxun
Abstract: The inhibition and control of combustible gas explosions is an issue of interest in the field of industrial and public safety. Based on a self-built twin-fluid water mist explosion suppression system in pipeline, this paper carried out a series of methane/air explosion inhibition experimental studies by N2 -twin-fluid water mist containing sodium chloride additive. The results showed that N2 -twin-fluid water mist containing sodium chloride additive could obtain an better inhibition effect on methane/air explosions. The reason was that: N2 -twin-fluid water mist containing sodium chloride additive enhanced the synergistic effects of physical and chemical inhibition. With the preferential diffusion and thermal effects of nitrogen, the flame speed was reduced, which prolonged the residence time of droplets in the flame zone and enhanced the cooling effect of the water mist; moreover, this prolonged the residence time of sodium chloride additive in the flame zone; therefore enhanced the heterogeneous chemistry and homogeneous chemistry inhibition effects on methane/air explosion.